Ischemic-Trained Monocytes Improve Arteriogenesis in a Mouse Model of Hindlimb Ischemia. Issue 2 (9th December 2021) - Falero-Diaz, Gustavo; Barboza, Catarina de A.; Pires, Felipe; Fanchin, Maeva; Ling, Jingjing; Zigmond, Zachary M.; Griswold, Anthony J.; Martinez, Laisel; Vazquez-Padron, Roberto I.; Velazquez, Omaida C.; Lassance-Soares, Roberta M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Monocytes, which play an important role in arteriogenesis, can build immunologic memory by a functional reprogramming that modifies their response to a second challenge. This process, called trained immunity, is evoked by insults that shift monocyte metabolism, increasing HIF (hypoxia-inducible factor)-1α levels. Since ischemia enhances HIF-1α, we evaluate whether ischemia can lead to a functional reprogramming of monocytes, which would contribute to arteriogenesis after hindlimb ischemia. Methods and Results: Mice exposed to ischemia by 24 hours (24h) of femoral artery occlusion (24h trained) or sham were subjected to hindlimb ischemia one week later; the 24h trained mice showed significant improvement in blood flow recovery and arteriogenesis after hindlimb ischemia. Adoptive transfer using bone marrow-derived monocytes (BM-Mono) from 24h trained or sham donor mice, demonstrated that recipients subjected to hindlimb ischemia who received 24h ischemic-trained monocytes had remarkable blood flow recovery and arteriogenesis. Further, ischemic-trained BM-Mono had increased HIF-1α and GLUT-1 (glucose transporter-1) gene expression during femoral artery occlusion. Circulating cytokines and GLUT-1 were also upregulated during femoral artery occlusion.Transcriptomic analysis and confirmatory qPCR performed in 24h trained and sham BM-Mono revealed that among the 15 top differentially expressed genes, 4 were involved in lipid metabolism in the ischemic-trained monocytes. Lipidomic analysis confirmed that ischemia training altered the cholesterol metabolism of these monocytes. Further, several histone-modifying epigenetic enzymes measured by qPCR were altered in mouse BM-Mono exposed to 24h hypoxia. Conclusions: Ischemia training in BM-Mono leads to a unique gene profile and improves blood flow and arteriogenesis after hindlimb ischemia.